1994
DOI: 10.2175/wer.66.5.3
|View full text |Cite
|
Sign up to set email alerts
|

Removal of zinc and manganese from contaminated water with cyanobacteria mats

Abstract: Cyanobacteria mats, developed for metal tolerance, were allowed to grow in columns packed with glass wool. Resulting columns contained complex, self-organized ecosystems dominated by cyanobacteria (blue-green algae). This immobilized cell system was assessed for its potential in removing zinc and manganese (mixed solution) from contaminated water. Twelve applications (days 2 to 13 of the experiment) of 0.3-L/day volumes containing 14 mg/L of each metal resulted in average removals of 96% zinc and 85% manganese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…In addition, cyanobacteria both adsorb and take up metals (Bender et al 1994), the active absorption may also contribute to the initial high accumulated amount and high BCF of the present results.…”
Section: Accumulation Amount Of Heavy Metalsmentioning
confidence: 56%
“…In addition, cyanobacteria both adsorb and take up metals (Bender et al 1994), the active absorption may also contribute to the initial high accumulated amount and high BCF of the present results.…”
Section: Accumulation Amount Of Heavy Metalsmentioning
confidence: 56%
“…The different response of autotrophic and heterotrophic components to Pb exposure could be related to Pb binding to DOM (Yoona et al, 1999), which could determine an increase of the bioavailability of this metal to heterotrophic bacteria that utilize DOM (Cho and Azam, 1990). Since previous studies reported that cyanobacteria, such as Spirulina platensis, can accumulate Hg and Pb in contaminated sites (Bender et al, 1994), an alternative explanation could be that Pb sequestration within the cell is coupled with the synthesis of metallothioneins that would considerably reduce the metal toxicity (Ybarra and Webb, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Work by House et al (1989) showed that coprecipitation of phosphate with calcium occurs in natural streams due to elevated pH brought about by algal photosynthesis. Elevated pH within algal biofilms may also contribute to precipitation of metals (Bender et al 1994, Liehr et al 1994.…”
Section: Role Of Algae In Solving the Problemmentioning
confidence: 99%